Indentation Depth Dependent Mechanical Behavior in Polymers. (17th August 2015) - Alisafaei, Farid; Han, Chung-Souk
Abstract : Various experimental studies have revealed size dependent deformation of materials at micro and submicron length scales. Among different experimental methods, nanoindentation testing is arguably the most commonly applied method of studying size effect in various materials where increases in the hardness with decreasing indentation depth are usually related to indentation size effects. Such indentation size effects have been observed in both metals and polymers. While the indentation size effects in metals are widely discussed in the literature and are commonly attributed to geometrically necessary dislocations, for polymer the experimental results are far sparser and there does not seem to be a common ground for their rationales. The indentation size effects of polymers are addressed in this paper, where their depth dependent deformation is reviewed along with the rationale provided in the literature.